Alloying of Alkali Metals with Tellurene. Issue 7 (27th December 2020) - Jain, Rishabh; Yuan, Yifei; Singh, Yashpal; Basu, Swastik; Wang, Dawei; Yang, Aijun; Wang, Xiaohua; Rong, Mingzhe; Lee, Ho Jin; Frey, David; Khadka, Rajan; Hundekar, Prateek; et al.
Abstract: Graphite anodes offer low volumetric capacity in lithium‐ion batteries. By contrast, tellurene is expected to alloy with alkali metals with high volumetric capacity (≈2620 mAh cm −3 ), but to date there is no detailed study on its alloying behavior. In this work, the alloying response of a range of alkali metals (A = Li, Na, or K) with few‐layer Te is investigated. In situ transmission electron microscopy and density functional theory both indicate that Te alloys with alkali metals forming A2 Te. However, the crystalline order of alloyed products varies significantly from single‐crystal (for Li2 Te) to polycrystalline (for Na2 Te and K2 Te). Typical alloying materials lose their crystallinity when reacted with Li—the ability of Te to retain its crystallinity is therefore surprising. Simulations reveal that compared to Na or K, the migration of Li is highly "isotropic" in Te, enabling its crystallinity to be preserved. Such isotropic Li transport is made possible by Te's peculiar structure comprising chiral‐chains bound by van der Waals forces. While alloying with Na and K show poor performance, with Li, Te exhibits a stable volumetric capacity of ≈700 mAh cm −3, which is about twice the practical capacity of commercial graphite. Abstract : The reaction of few‐layer tellurene with alkali metals is investigated. Surprisingly, a single‐crystal Li2 Te product is obtained, which is very rare during alloy formation. This behavior is explained based on the isotropic transport of Li within the Te structure. It is also shown that Te offers superior volumetric performance when compared to traditional graphite anodes in lithium‐ion batteries.